Anti-Inflammatory Activity of Dolichos lablab Beans: A Perspective Based on T Lymphocytes Profiles - Purwanti, Elly; Nuryady, Moh Mirza; Permana, Tutut Indria; Rachmawati, Farida; Ariesaka, Kiky Martha; Hermanto, Feri Eko (HAYATI Journal of Biosciences, 2026)
Dolichos lablab has several known therapeutic properties, but further exploration is needed to clarify its exact anti-inflammatory activity. Since excessive inflammation might worsen many pathological conditions, profiling immune cell regulation, such as T lymphocytes, is critical. This study evaluated the anti-inflammatory activity of Dolichos lablab extract (DLE) based on CD4 and CD8 cell populations. Fifteen male BALB/c mice were divided into five groups: untreated (N), injected with Escherichia coli (1 × 106 CFU/mouse, i.p., 250 µL) (I), treated with different doses of DLE (250, 500, 1000 mg/kg BW), followed by E. coli injection defined as group D1, D2, and D3 respectively. The splenocytes were collected for immunostaining, and CD4 and CD8 lymphocytes were quantified by flow cytometry (FCM). FCM data were analyzed using BDFacs Flow and one-way ANOVA with LSD post-hoc test. DLE treatment suppressed the total number of cells and activated the CD4 and CD8 populations, even after E. coli injection. The low dose of DLE (250 mg/kg BW) kept lymphocyte levels near normal, with higher doses showing no significant difference. DLE also decreased the CD4/CD8 ratio. In conclusion, DLE demonstrated measurable anti-inflammatory activity in mice, suggesting its potential as a candidate for further preclinical evaluation.